2009
DOI: 10.1242/jeb.027896
|View full text |Cite
|
Sign up to set email alerts
|

Dolphins maintain cognitive performance during 72 to 120 hours of continuous auditory vigilance

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…The right side is always larger (Mead, 1975). The preponderance of observations show that dolphins make pulsed sounds on the right side of the nose and whistles on the left (Ridgway et al, 2009;Madsen et al, 2013). Cranford et al…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The right side is always larger (Mead, 1975). The preponderance of observations show that dolphins make pulsed sounds on the right side of the nose and whistles on the left (Ridgway et al, 2009;Madsen et al, 2013). Cranford et al…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have previously found that unihemispheric sleep includes the corticothalamic areas of the brain (Ladygina and Supin, 1977;Supin et al, 1978). Furthermore, the studies of Branstetter et al (2012) and Ridgway et al (2006Ridgway et al ( , 2009 demonstrated that dolphins might be able to respond to echoes or to presented tones continuously, despite the necessity for sleep. They get essential sleep critical for homeostasis and for maintaining awareness by engaging in unihemispheric sleep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased number of glial cells in the cetacean brain, as seen herein when compared to artiodactyls, may result in an increased production of lactate. This extracellular lactate may be related to maintained arousal and attention during unihemispheric sleep (Ridgway et al, 2006(Ridgway et al, , 2009Branstetter et al, 2012), as extracellular lactate concentrations are higher during periods of wake (Pellerin and Magistretti, 1994). Furthermore lactate reduces extracellular pH levels and this is vital for arousal and attention, as orexinergic neurons are excited by a low pH (Williams et al, 2007;Parsons and Hirasawa, 2010).…”
Section: Orexinergic Bouton and Glial Cell Density Interaction In Thementioning
confidence: 99%
“…Additionally, it has been demonstrated that dolphins can continuously maintain vigilant behaviour for at least 15 days without any signs of sleep deprivation (Ridgway et al, 2006(Ridgway et al, , 2009Branstetter et al, 2012), an observation not made, but unlikely to be present in artiodactyls.…”
Section: Introductionmentioning
confidence: 99%